FACTORS ASSOCIATED WITH SITUATION AWARENESS AMONG NURSES IN INPATIENT SETTINGS: A SCOPING REVIEW - Nina Risnianingsih; Ayu Prawesti Priambodo; Etika Emaliyawati (Pena Cendekia Insani, 2026)
Situation awareness (SA) is a critical cognitive skill for nurses in inpatient settings, where patient conditions are complex and can change rapidly. Adequate SA enables nurses to perceive, comprehend, and anticipate clinical situations, supporting timely decision-making and patient safety. However, evidence on factors associated with nurses’ SA across inpatient settings remains fragmented. This scoping review aimed to identify, map, and synthesize these factors. The review followed the Arksey and O’Malley framework and was reported according to PRISMA-ScR guidelines, with eligibility structured using the Population–Concept–Context (PCC) framework. PubMed, Scopus, and EBSCOhost were searched up to 3 January 2026 for studies examining SA or related constructs among nurses in inpatient settings. Data were extracted and analyzed using descriptive and thematic synthesis. Twelve of 2,615 studies were included, published between 2012 and 2025. Five major categories of factors emerged: individual, information- and technology-related, communication and teamwork, organizational, and environmental. These interact dynamically and influence all three levels of SA. Nurses’ SA is therefore a multifactorial, dynamic construct, and enhancing it requires a system-level approach extending beyond individual competencies to information systems, team communication, and organizational support.